Diversity in employment of electric commercial vehicles in urban freight transport: A literature review - Molin Wang; Klaus-Dieter Thoben; Marcella Bernardo; Morice Daudi (Logistics Research, 2018)
Employment of Electric Commercial Vehicles (ECVs) constitutes measures to achieve sustainable Urban Freight Transport (UFT). Despite a critical need for ECVs, in industry, the market penetration of ECVs in UFT has remained relatively low. To increase such market penetration, one crucial issue to consider is to obtain a satisfactory match between characteristics of ECVs and requirements of UFT. However, matching diverse types of ECVs and various delivery tasks in UFT leads to many possibilities. The present paper refers to such possibilities as diversity and denotes them as ECV-UFT combinations. Potentials inherent in this diversity seem ignored by the majority of the literature. Therefore, the present paper explores the significance of studying such diversity for the market penetration. In particular, the paper identifies the primary areas of focus and the extent of the diversity already considered in the literature. To accomplish this identification, a Systematic Literature Review (SLR) is applied. The SLR follows a sequence of activities, including selecting sources and keywords, as well as classifying and summarizing results. Findings unveil that the literature has primarily focused on issues concerning the feasibility of ECVs, the adaptation of logistics and vehicle concepts, and support of stakeholders. Furthermore, little consideration of the diversity in the employment of ECVs in UFT is observed as a consequence accounting for the low market penetration. Finally, building on the diversity to increase market penetration, the paper proposes to extend ECV-UFT combinations in the outlined primary areas of focus as future research work.
Keywords: 650; electric commercial vehicles; sustainable urban freight transport; market penetration; diversity